URGENT PROPHYLAXIS, PATHOGENETIC TREATMENT AND PREVENTION OF COMPLICATIONS OF INFLUENZA AND ACUTE RESPIRATORY INFECTIONS IN CHILDREN - V. V. Chernikov (Вопросы современной педиатрии)
Influenza — is an acute viral infection, transmitted by droplet contact. Influenza virus is characterized by its ability to provoke yearly seasonal epidemics, which have great influence on all age populations and are a significant problem for the public health care. This disease can lead to development of severe complications, especially in infants. There are two methods of influenza prophylaxis — specific (vaccination) and non-specific (immunotropic agents). The article contains data on usage of the Russian antiviral agent, which stimulates non-specific protection against influenza virus and other causative agents of respiratory viral infections, especially in infants. A new powder form of the drug which can be used in children from the 1st year of life is represented in the article.